Diez años de la revista "Enseñanza de las Ciencias": de una ilusión a una realidad - Moreira, Marco Antonio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This paper is essentially the sequence of overhead transparencies used in the opening speech of the IV International Congress on Research in the Didactics of Science and Mathematics, held in Barcelona, September 13-16, sponsored by the "Enseñanza de las Ciencias" journal. The theme of the speech was a critical analysis of the first ten years, 1983-1992, of this journal. Initially, the analysis focuses on general aspects of the journal such as its policies, its political positions, the language issue, the emphasis on research on teaching, the kinds of papers published, and the subjects of these papers. Then, the focus moves to a critical view of the research papers concerning their theoretical and methodological bases.